2022
DOI: 10.1007/s12144-022-03473-5
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and harms of social media use: A latent profile analysis of emerging adults

Abstract: The rise in social media use among emerging adults in the United States has been well-documented, but researchers are still working on identifying how the type—not just the frequency—of use impacts psychological well-being. We identified “profiles” of social media use among young adults based on the frequency and purposes of use, and examined their associations with benefits and harms to psychosocial well-being, using data from 2828 incoming undergraduate students (Mage = 18.29 years; age range: 17 to 25 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…Given the rapid spread and popularity of social media [ 67 ], the scientific community is vigilant and active in investigating how the use of these tools can promote subjective well-being or, on the contrary, lead to problematic behaviors and disorders [ 68 ]. The present study fits into this line of research, focusing on the factors that may be associated with social media addiction by investigating the role of alexithymia, body image concern, and self-esteem, controlling for age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rapid spread and popularity of social media [ 67 ], the scientific community is vigilant and active in investigating how the use of these tools can promote subjective well-being or, on the contrary, lead to problematic behaviors and disorders [ 68 ]. The present study fits into this line of research, focusing on the factors that may be associated with social media addiction by investigating the role of alexithymia, body image concern, and self-esteem, controlling for age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…The internet’s facilitation of greater access and exposure to online racism also likely contributes to a heightened sense of loneliness among people. With the increasing reliance on and salience of digital communication as a means of social interaction among emerging adults, loneliness has been significantly correlated with social media use (Keum et al, 2022; Yang & Robinson, 2018). Social media use may evoke greater feelings of loneliness and social isolation among individuals who feel ostracized from online interactions (e.g., cyber aggression) and are frequently exposed to violent media that shape an unsafe outlook of their surrounding communities (e.g., violence in communities; Lim et al, 2020).…”
Section: Distress Alcohol Use Severity and Loneliness Associated With...mentioning
confidence: 99%
“…These trends seem to suggest an inverse U-shaped relationship where the moderate engagement group may be indicating an optimal level of online social support seeking and advocacy engagement with the lowest risk of alcohol use; beyond which, our anticipation of lower alcohol use severity with greater online social support seeking and advocacy engagement was not the case. Social media use studies have consistently found that active users are likely to retain both benefits and costs impacting their well-being (e.g., [54,55]). Specifically, given the significantly higher online social support seeking reported by individuals who may be in the triggered/reactive group compared to the moderate group, this trend may be related to the active process of seeking online support.…”
Section: Plos Onementioning
confidence: 99%